MANAJEMEN ISU TERKAIT PEMBERITAAN KEBAKARAN HUTAN DAN LAHAN HUMAS PT.RAPP DALAM MEMPERTAHANKAN CITRA PERUSAHAAN DI PROVINSI RIAU - ", Astiyo; Firdaus, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The development of issues through mass media both printed and online on the issue of forest fires and RAPP land can have a negative impact on the company's image. The emergence of various negative news through the mass media both print and electronic about PT. Riau Andalan Pulp and Paper related to forest and land fire issues RAPP can give negative reaction to public company in responding to media coverage. Therefore the company must have an effective issue management strategy to respond to the problem. The purpose of this research is to know the strategy of Corporate Communications Department of PT.RAPP in determining the strategy of problem management planning, issue management implementation and supervision of issue management through communication strategy activity related to the development of negative issue of forest fire and RAPP land.The research method used in this research is qualitative method by assigning 5 (five) subject of research as informant through purposive technique. Management Strategy Public Relations Issues PT.RAPP In Maintaining Company Image Related News Forest Fire and Land in Riau Province. Information data obtained through observation, interviews, documentation. Data analysis techniques in this study using interactive data model Miles & Huberman. Data validation checks use optical elongation and triangulation techniques.The results show that the Corporate Communications Department's issues management strategy is done by taking a planning strategy with environmental monitoring, gathering data around issues and developing communication strategies. Implementation is done by developing proactive policies, analyzing organizational relationships with stakeholders, preparing contingency plans and setting messages, goals and media. Supervision is conducted by monitoring issues that threaten and monitor the dynamics of issues, media monitoring, socialization and evaluation.